Reburial of nonexistents : reconsidering the Meinong-Russell debate - Swanson, Carolyn. (Value Inquiry Book Series, 2011)
Alexius Meinong claimed to uncover a brave new world of nonexistent objects. He contended that unreal objects, such as the golden mountain and the round square, genuinely had properties (such as nonexistence itself) and therefore, deserved a place in an all-inclusive science. Meinong's notion of nonexistents was initially not well-received, largely due to the influence and criticisms of Bertrand Russell. However, it has gained considerable popularity in more recent years as academics have uncovered shortfalls in Russell's philosophy and strived to explain apparent "facts" about the beingless. Some philosophers have continued Meinong's project, further explaining nonexistent objects or formulating logic systems that incorporate them. The more recent developments beg for a re-examination of Meinongianism. This book does just that, putting the theory on trial. Part One considers if Russell truly defeated Meinongianism. It addresses Meinongian rejoinders in response to Russell's main criticisms and further defends Russell's alternative solution, his Theory of Descriptions. Part Two explores the rationale for nonexistents and their use in interpreting three types of statements: characterization, negative existential, and intentional. The book argues that, despite appearances, Meinongianism cannot plausibly account for its own paradigm claims, whereas Russell's framework, with some further elucidation, can explain these statements quite well. Part Three primarily addresses claims about fiction, exploring the short-comings of Meinongian and Russellian frameworks in interpreting them. The book introduces a contextualization solution and symbolic method for capturing the logical form of such claims - one with the complexity to handle cross-contextual statements, including negative existential and intentional ones. It finally considers where that leaves nonexistent objects, ultimately rejecting such so-called entities.